2022
DOI: 10.4038/cjs.v51i3.8035
|View full text |Cite
|
Sign up to set email alerts
|

Development of antibacterial polymer composite films from cassava starch and silver vein graphite composite

Abstract: Nowadays starch based natural polymers have been received tremendous attention owing to their non-toxicity, biodegradability, and biocompatibility. However, the applications of starch-based films are restricted due to water sensitivity and bacterial contaminations. To overcome these issues, a polymer composite film was produced by solution casting using cassava starch and silver vein graphite composite. The incorporation of silver vein graphite composite into cassava starch showed a reduction in water absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…However, as mentioned above, the number of interactions between the starch chains and Ag nanoparticles is small. Senevirathna et al found that a silver vein graphite composite could act as a filler but that it did not chemically bind to starch chains [74].…”
Section: Chemical Structurementioning
confidence: 99%
“…However, as mentioned above, the number of interactions between the starch chains and Ag nanoparticles is small. Senevirathna et al found that a silver vein graphite composite could act as a filler but that it did not chemically bind to starch chains [74].…”
Section: Chemical Structurementioning
confidence: 99%